Institucional and jurisprudential protection and recognition of the human right to the health in the penitential and prison establishment of Tunja. - Rodríguez Forero, Nicolás David (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The field of protection, recognition and responsibility of the human right to health for persons deprived of liberty in the context of Tunja, allows us to explore and explain the institutional intervention on the fundamental scope of this right, taking the institutional, administrative, judicial and humanitarian control bodies' visions, such as the EPMSC of Tunja, the Municipal Ombudsman, the Ombudsman's Office and the Health Secretariat of Boyacá within the framework of the unconstitutional state of affairs and the protection of this population group in the context of the legal and constitutional articulation in the period 2002-2019.